The impact of faculty international competence and organizational support on faculty engagement in internationalization at private universities in China: A conceptual framework - Nannan Wang; Siew Nyet Moi @ Sopiah Abdullah; Nan Zhang (Global Academic Excellence, 2025)
In the process of internationalization at private universities in China, the level of faculty engagement remains challenged by various factors. This study integrates organizational support theory and the Ability-MotivationOpportunity theory to propose a conceptual framework that assesses the impact mechanisms of faculty international competence and organizational support on faculty engagement in internationalization, with a particular focus on the mediating role of organizational support through international competence. The findings indicate that faculty international competence significantly influences their willingness and depth of participation in international activities; organizational support not only directly promotes faculty engagement in internationalization but also indirectly enhances their participation levels by improving their international competence. The constructed framework provides theoretical support for understanding the influencing factors of faculty engagement in internationalization at private universities in China and offers practical guidance on how institutions can optimize policies and resource allocation to promote faculty engagement. Future research could empirically test this framework to further explore the strength of relationships among variables and their mechanisms.